2021
DOI: 10.1021/acsnano.1c01146
|View full text |Cite
|
Sign up to set email alerts
|

Janus Nanoparticles: From Fabrication to (Bio)Applications

Abstract: Janus nanoparticles (JNPs) refer to the integration of two or more chemically discrepant composites into one structure system. Studies into JNPs have been of significant interest due to their interesting characteristics stemming from their asymmetric structures, which can integrate different functional properties and perform more synergetic functions simultaneously. Herein, we present recent progress of Janus particles, comprehensively detailing fabrication strategies and applications. First, the classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 445 publications
0
129
0
Order By: Relevance
“…Representation of types, used materials, fabrication methods and utilization areas of Janus surfaces [7]. …”
Section: Bio‐based Polymers To Fabricate Janus Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Representation of types, used materials, fabrication methods and utilization areas of Janus surfaces [7]. …”
Section: Bio‐based Polymers To Fabricate Janus Structuresmentioning
confidence: 99%
“…Furthermore, the controllable and tunable properties of those nature‐derived compounds with external inductions such as light, pH, temperature or ionic strength increased the attention on these polymers, not only for traditional usage in chemistry, textile and material science but also for biomedical applications [6]. Recently, the applications of bio‐compatible nature‐derived polymers as Janus structures for bio‐based applications might be listed as solid surfactants, micro/nano motors, biosensing, drug delivery, bioimaging, cancer therapy and theragnostic [7]. In addition to bio‐based applications of nature‐derived and bio‐compatible Janus structures, the potential of food‐grade polymers to be processed into a Janus form were of great interest, lately [1, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Janus particles (JPs) are a unique type of nanomaterials that combine two or more physical or chemical properties in the same entity, resulting in unpreceded capabilities [ 1 ]. The concept “Janus Particle” to define anisotropic materials was pioneered by the Nobel Laureate Pierre-Gilles de Gennes during his lecture about “Soft matter.” Among other findings, Gennes synthetized the first JP consisting of a glass bead with polar and non-polar hemispheres [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on the analytical dimension of JPs and JMs for enhanced (bio)sensing. The reader is referred to current recent reviews to expand the dimension of JPs and JMs in other fields [ 1 , 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key to this approach was to accurately control the internal structure of the particles. Many studies have reported the application of Janus particles in drug delivery systems [ 16 18 ]. In contrast to ordinary particles, Janus particles show unique advantages in that it is possible to precisely control their internal cavity structures, owing to their anisotropy and dual functions.…”
Section: Introductionmentioning
confidence: 99%